LEARNING MOTIVATION IN THE MERDEKA CURRICULUM: THE ROLE OF LEARNING STYLES AND SELF-CONFIDENCE AMONG FIFTH GRADE STUDENTS - Rahma Darini; Yera Putri Rahayu (El-Ibtidaiy: Journal of Primary Education, 2026)
Learning motivation is a fundamental factor that determines students’ engagement, persistence, and success in the learning process, particularly at the elementary school level where basic learning attitudes are formed. Within the implementation of the Merdeka Curriculum, which emphasizes student-centered learning, differentiation, and holistic development, understanding factors related to learning motivation becomes increasingly important. This study aims to examine the role of learning styles and self-confidence in influencing learning motivation among fifth grade students of SD Negeri 011 Pangkalan Kuras. This research employed a quantitative approach with a correlational design involving 114 fifth grade students. Data were collected using questionnaires measuring learning styles, self-confidence, and learning motivation that were adapted to the characteristics of elementary school students. The data were analyzed using descriptive statistics and multiple regression analysis. The results indicate that self-confidence has a significant positive effect on students’ learning motivation, while learning styles do not show a significant effect when examined independently. However, learning styles and self-confidence simultaneously demonstrate a significant relationship with learning motivation, although their contribution is relatively small. These findings suggest that strengthening students’ self-confidence is a key strategy for enhancing learning motivation within the Merdeka Curriculum context at the elementary school level. Keywords: learning motivation, learning styles, self-confidence, Merdeka Curriculum, elementary school students